EXPORT POTENTIAL OF SMALL ENTERPRISES - MUSREDINOVA, TAMILA (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The most important directions of the economic policy of each country at the present stage are the development of exports, increasing the competitiveness of domestic products in the foreign market. It is precisely in conditions of fierce competition and external restrictions that the export potential should be activated, primarily due to the most mobile component of the economy – small and medium-sized businesses. To achieve these objectives, it is necessary to stimulate and involve successful and competitive enterprises (especially those with innovative and high-tech products/services) in the field of foreign economic activity, to promote the realization of their export potential, to improve the qualifications and knowledge of their employees in the field of foreign economic activity.